Systematic literature review: analisis soal matematika materi bilangan bulat ditinjau dari kemampuan berpikir kreatif siswa - Pamungkas, Dwi; Ginting, Riska Natasi Br; Fariha, Naela Faza (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to evaluate students’ creative thinking abilities in solving mathematical problems related to the topic of integers using the Systematic Literature Review (SLR) method. The SLR involved critically analyzing 15 relevant scientific articles published in the last five years. The findings reveal that students’ overall creative thinking ability remains at a low level, particularly in the indicators of originality and elaboration. Most students are only able to demonstrate fluency in generating answers, but they struggle to produce unique solutions or elaborate ideas in depth. Several factors contribute to this condition. First, most math problems used in schools are closed-ended, emphasizing one correct answer and failing to encourage idea exploration. Second, teaching approaches still tend to be procedure-oriented, training students to memorize steps rather than understand underlying concepts. Third, internal student factors such as low academic confidence and limited problem-solving skills also hinder the development of creative thinking. This study suggests the importance of designing open-ended, contextual, and challenging problems to stimulate all aspects of creative thinking, including fluency, flexibility, elaboration, and originality. Furthermore, teachers are encouraged to adopt more explorative and student-centered approaches in the classroom to foster a culture of creative thinking from an early stage of learning.